2017
DOI: 10.3233/npm-16170
|View full text |Cite
|
Sign up to set email alerts
|

Haddad syndrome novel association with BRAF mutation

Abstract: This is a report of a 36 week male infant who suffered abdominal distension and difficulty opening bowels within first few days of life and showed a pattern of hypoventilation and apnea associated with sleep. His diagnostic studies confirmed the diagnosis of congenital central hypoventilation syndrome CCHS (PHOX2B mutation) and Hirschsprung's disease and later found a further mutation of BRAF oncogene. This describes a novel association between these mutations and the shared qualities of tumorigenesis between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The variable phenotypes reported in CCHS patients carrying the same mutation also suggest the involvement of modifier genes of expressivity (Di Lascio et al, 2018a;Bachetti and Ceccherini, 2020). Mutations in genes other than PHOX2B, involved in the differentiation of neural crest cells (RET, GDNF, BDNF, GFRA1, PHOX2A, HASH-1, EDN1, EDN3, BMP2) or in oncogenes (BRAF) (Bolk et al, 1996;Amiel et al, 1998;Weese-Mayer et al, 2002Sasaki et al, 2003;Fernández et al, 2013;Al Dakhoul, 2017) have been found in some CCHS individuals. Remarkably, some of them are PHOX2B target genes (Flora et al, 2001;Bachetti et al, 2005), but the pathogenic role of these genetic variants is unclear (de Pontual et al, 2007).…”
Section: Congenital Central Hypoventilation Syndrome (Cchs): Clinicalmentioning
confidence: 96%
“…The variable phenotypes reported in CCHS patients carrying the same mutation also suggest the involvement of modifier genes of expressivity (Di Lascio et al, 2018a;Bachetti and Ceccherini, 2020). Mutations in genes other than PHOX2B, involved in the differentiation of neural crest cells (RET, GDNF, BDNF, GFRA1, PHOX2A, HASH-1, EDN1, EDN3, BMP2) or in oncogenes (BRAF) (Bolk et al, 1996;Amiel et al, 1998;Weese-Mayer et al, 2002Sasaki et al, 2003;Fernández et al, 2013;Al Dakhoul, 2017) have been found in some CCHS individuals. Remarkably, some of them are PHOX2B target genes (Flora et al, 2001;Bachetti et al, 2005), but the pathogenic role of these genetic variants is unclear (de Pontual et al, 2007).…”
Section: Congenital Central Hypoventilation Syndrome (Cchs): Clinicalmentioning
confidence: 96%